Self and self-consciousness: Aristotelian ontology and Cartesian duality - Christofidou, A (2009)
The relationship between self-consciousness, Aristotelian ontology, and Cartesian duality is far closer than it has been thought to be. There is no valid inference either from considerations of Aristotle's hylomorphism or from the phenomenological distinction between body and living body, to the undermining of Cartesian dualism. Descartes' conception of the self as both a reasoning and willing being informs his conception of personhood; a person for Descartes is an unanalysable, integrated, self-conscious and autonomous human being. The claims that Descartes introspectively encounters the self and that the Cartesian extent of inner space is self-contained are profound errors, distortions through the lenses of modern theories. © 2009 Blackwell Publishing Ltd.